In vitro study of some plant extracts against Alternaria brassicae and Alternaria brassicicola - Sasode, R S; Prakash, Sweta; Gupta, Amod; Pandya, R K; Yadav, Amit (Journal of Phytology, 2012)
Madhya Pradesh is an important rapeseed-mustard producing state of India contributing nearly of the total production in the country. The present study aims to evaluate the effectiveness of some botanicals viz., Neem, Eucalyptus, Datura, Pudina, Tulsi, Lantana under crude and Forms @ against 10% Alternaria brassicae under in vitro condition by poisoned food technique. Neem and Eucalyptus were also evaluated in the oil forms.Â Nearly all the tested botanicals found effective against these fungi. Among the crude extract 10 per cent the minimum growth was recorded in Neem followed by Eucalyptus, Tulsi, Lantana, Datura and Pudina. Neem was significantly superior over Tulsi, Lantana, Datura and Pudina but at par with Eucalyptus. Under boil forms the minimum radial growth was also recorded in Neem. The oil extract (Neem and Eucalyptus) were found less effective as compared to crude and boil extracts.